Influence of Corporate Reputation and Direct Marketing on Purchse Decision Air Service Cargo at PT Angkasa Pura Logistics Semarang Branch - Sekar, Sany -; Nurkhayati, Isnaini -; Nahar, M - (Politeknik Negeri Semarang, 2024)
This study aims to determine the influence of corporate reputation and direct marketing on purchase decision at PT Angkasa Pura Logistics Semarang Branch. The sampling technique used total sampling of 36 respondents. The independent variables of the research are corporate reputation and direct marketing. Meanwhile the dependent variable of the research is purchase decision. Primary data collection using questionairre as well as literature studies for secondary data. The analytical method used is validity test, reliability test, descriptive analysis, classical assumption test, multiple linear regression, t test, F test and coefficient of determination. Based on the calculations that have been done using SPSS 25 version, the regression equation is Y = 3,096 + 0,50X1 + 0,427X2 + e. The Result of the t test show that the calculated t value is greater than t table value and produces a significance value of less than 0,05. The result of the F test shows that the calculated F value is 28,870 while the F table is 3,28. So it can be concluded that corporate reputation (X1) and direct marketing (X2) have a positive and significant effect on purchase decisions (Y). the influence of the independent variable that influences purchasing decisions dominantly is the corporate reputation variable with a regression coefficient of 0,50